Letter from Georg Bredig to Max Bredig, May 30, 1927 - Bredig, Georg (1927)
Georg Bredig (1868-1944) provides professional advice and references to his son, Max Bredig (1902-1977). Georg additionally warns that antisemitism exists at universities, but that his son should remain confident and diligent in his work.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977